Enhancing Students’ Awareness and Interest in Information Security: The Role of Culturally Relevant Instructional Strategy - Gbeleyi, Olasunkanmi A.; Foli, Jessie Yao; Akintolure, Stephen. O.; Oladejo , Adekunle I.; Ariyibi, Olanrewaju Olasupo (FKIP - Universitas Riau, 2025)
This study examines the integration of information security awareness and interest in educational settings, focusing on how classroom practices can align with cultural relevance and innovative teaching methods. It compares two teaching approaches to assess their impact on awareness and student interest in ICT, particularly Information Security. It specifically evaluates the Culturo-Techno-Contextual Approach (CTCA), which combines culture, technology, and context, to enhance Ghanian Junior High School students' awareness and interest in Information Security. The study investigates whether CTCA can foster deeper learning and boost students’ engagement in information security. A total of 106 students participated, with 54 in the experimental group and 52 in the control group. As random assignment was not feasible, an ancova analysis was conducted, using pretest scores as a covariate. The findings showed that the CTCA method was more effective than traditional teaching, with a significant improvement in students awareness and interest in Information Security (F (1, 103) = 3.91; p = .05). The intercept was highly significant (p < 0.001). Based on these results, the study suggests adopting the CTCA approach in Sub-Saharan Africa to improve students’ awareness and interest in ICT and related subjects.